Nordic Research Cooperation : Climate Change and its Consequences in the Arctic (Copenhagen : Nordic Council of Ministers, 2007)
Short version in English of the report: TemaNord 2007:580 "Nordiskt forskningssamarbete om klimatförändringen och dess konsekvenser i Arktis"